Hermeneutika Hans-Georg Gadamer dan Relevansinya dengan Rekonstruksi Pola Komunikasi Dakwah - Khasri, Muhammad Rodinal Khair; Yamaraja, Bernard Selfry (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, IAI Al-Qodiri Jember, 2024)
This study is qualitative research based on a literature review. It addresses the problem of relativism of truth and hegemonic patterns in da'wah communication. In response to this issue, using Gadamer's hermeneutic approach, this research aims to reconstruct the pattern of da'wah communication to moderate the tension between conservatism and progressivism. Moderation takes place at the hermeneutic level, referring to the process of communicators interpreting their reality and the reality of the recipients. This interpretation involves three important moments: 1) Bildung or cultural constellation shaping the interpreter's horizon and referring to the intellectual progress of both communicators and recipients, 2) historical influence as an existential moment for communicators and recipients, clarifying that dialogue must consider context, 3) fusion of horizons showing that there is no final understanding of everything. The most important thing is the endless process.